1966
DOI: 10.1093/bja/38.6.463
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Sugar Response to Anaesthesia and Surgery in Southern Indians

Abstract: SUMMARYDuring the course of anaesthesia and surgery in South India, it was noticed that Indian and European patients responded differently. In an attempt to evaluate these differences, blood sugar values were used as a guide to the sympathetic nervous response. Under general anaesthesia values rose and stayed higher in Indian patients than in Europeans in India or England. General anaesthesia by itself provoked no elevation until the commencement of surgical trauma. Under subarachnoid or epidural analgesia, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1968
1968
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Furthermore, the latter two groups have also shown that glucose metabolism is not impaired by thiopentone anaesthesia, and discrepancies between workers may be attributed to species variation and the use of very high dosage in animals. Race of patient and site of operation also influence the response (Keating, 1958;Keating, Patrick and Annamunthodo, 1959;Cullingford, 1966) but whether the rise is harmful, as these workers have suggested, remains an open question. It would seem worth investigating whether the hyperglycaemic reaction is related to the amount of trauma, and whether it can be prevented, if only to understand more about its mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the latter two groups have also shown that glucose metabolism is not impaired by thiopentone anaesthesia, and discrepancies between workers may be attributed to species variation and the use of very high dosage in animals. Race of patient and site of operation also influence the response (Keating, 1958;Keating, Patrick and Annamunthodo, 1959;Cullingford, 1966) but whether the rise is harmful, as these workers have suggested, remains an open question. It would seem worth investigating whether the hyperglycaemic reaction is related to the amount of trauma, and whether it can be prevented, if only to understand more about its mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…[6910] Such concentrations may be obtained shortly after the injection of clinical doses of adrenaline containing LA. [611]…”
Section: Discussionmentioning
confidence: 99%
“…[123456789101112131415161718192021222324252627] The present study was done to comparatively evaluate the effects of 2% lignocaine and 2% lignocaine with 1:200,000 epinephrine on blood glucose level and hemodynamics in patients undergoing multiple tooth extractions.…”
Section: Introductionmentioning
confidence: 99%
“…Among the above mentioned responses, hyperglycemia can be detrimental to the well-being of the patient. 9,10 Hyperglycemia can potentiate brain, spinal cord and renal damage by ischemia.…”
Section: Introductionmentioning
confidence: 99%